Alfabetização Científica e Tecnológica na formação inicial de professores de química - Oliveira, Ana Carolina Dias de (Universidade Federal de São Carlos, 2019)
The Scientific and Technological Literacy (ACT) has been much discussed in Science Teaching and, little by little, is being inserted as a purpose in the curricula of basic education. However, higher education still lacks many studies that favor the inclusion of approaches that promote TCA. Because it is something to be developed throughout the life of the citizens, ACT should be present at all stages of teaching. In higher education, we emphasize the importance of this approach in teacher training courses, undergraduate courses. A student in a bachelor's degree who is unfamiliar with ACT's assumptions and who is not exposed to ways to develop it will hardly be able to promote it with his prospective students, resulting in a chain problem throughout the educational system. Given the relevance of this training, many studies are developed in order to develop strategies for promoting ACT in Science Teaching, such as the Interdisciplinary Island of Rationality (IIR), proposed by Fourez (2005). Taking into consideration the aforementioned notes, we seek, in this work, to make a bibliographical survey to identify aspects necessary in the training of graduates from the ACT perspective. From these aspects, the ACT process indicators were developed for teachers in training, to be considered in the analysis of information obtained through semi-structured interviews with students of the Licentiate in Chemistry course. The purpose of creating these indicators, and using them in the interviews, is to be able to create a parameter that identifies a training of a licentiate to promote ACT. In this work, it was also specially evaluated how an IIR may or may not contribute to training in this sense, and can be used as a teaching strategy in undergraduate courses. The results pointed out that a reflexive formation is fundamental so that we can have graduates qualified to promote ACT, since this type of formation can lead in several actions of the future teachers that involves the aspects indicated in this dissertation as necessary for the promotion of ACT, in addition the IIR was evaluated as a good methodological strategy to favor this reflexive formation and in favor of ACT.
Keywords: Ensino superior; Formação de professores; Ensino de ciências; Ensino de química; Metodologia do ensino; Higher education; Teacher training; Science teaching; Chemistry teaching; Teaching methodology; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO